Targeting of intragraft reactive oxygen species by APP‐103, a novel polymer product, mitigates ischemia/reperfusion injury and promotes the survival of renal transplants. Issue 6 (22nd February 2020) - Minami, Koichiro; Bae, Soochan; Uehara, Hirofumi; Zhao, Chen; Lee, Dongwon; Iske, Jasper; Fanger, Michael W.; Reder, Jake; Morrison, Ian; Azuma, Haruhito; Wiens, Astrid; Van Keuren, Edward; et al.
Abstract : Inflammatory responses associated with ischemia/reperfusion injury (IRI) play a central role in alloimmunity and transplant outcomes. A key event driving these inflammatory responses is the burst of reactive oxygen species (ROS), with hydrogen peroxide (H2 O2 ) as the most abundant form that occurs as a result of surgical implantation of the donor organ. Here, we used a syngeneic rat renal transplant and IRI model to evaluate the therapeutic properties of APP‐103, a polyoxalate‐based copolymer molecule containing vanillyl alcohol (VA) that exhibits high sensitivity and specificity toward the production of H2 O2 . We show that APP‐103 is safe, and that it effectively promotes kidney function following IRI and survival of renal transplants. APP‐103 reduces tissue injury and IRI‐associated inflammatory responses in models of both warm ischemia (kidney clamping) and prolonged cold ischemia (syngeneic renal transplant). Mechanistically, we demonstrate that APP‐103 exerts protective effects by specifically targeting the production of ROS. Our data introduce APP‐103 as a novel, nontoxic, and site‐activating therapeutic approach that effectively ameliorates the consequences of IRI in solid organ transplantation. Abstract : APP‐103, a novel polymer product, is shown to be safe and effective in improving organ functionality following ischemia‐ reperfusion injury in models of syngeneic transplantation.